2018
DOI: 10.1177/1740774518761627
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and reporting of recruitment, randomisation and treatment errors in clinical trials: A systematic review

Abstract: Background/aims In clinical trials, it is not unusual for errors to occur during the process of recruiting, randomising and providing treatment to participants. For example, an ineligible participant may inadvertently be randomised, a participant may be randomised in the incorrect stratum, a participant may be randomised multiple times when only a single randomisation is permitted or the incorrect treatment may inadvertently be issued to a participant at randomisation. Such errors have the potential to introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 13 publications
(40 reference statements)
2
19
0
Order By: Relevance
“…Of the remaining findings, a large proportion related to patient eligibility (recognised as a problem in other trials), 29 unreported serious adverse events and unreported time-to-event endpoints (in these RCTs, death or cancer progression). Processes to check eligibility prior to randomisation include collection of more detailed data on trial forms to verify eligibility (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining findings, a large proportion related to patient eligibility (recognised as a problem in other trials), 29 unreported serious adverse events and unreported time-to-event endpoints (in these RCTs, death or cancer progression). Processes to check eligibility prior to randomisation include collection of more detailed data on trial forms to verify eligibility (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining findings, a large proportion related to patient eligibility (recognised as a problem in other trials 28 ), unreported Serious Adverse Events and unreported time-to-event endpoints (in these RCTs, death or cancer progression). Processes to check eligibility prior to randomisation include collection of more detailed data on trial forms to verify eligibility (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…During data preprocessing for multi-omics data integration, our analyses suggested that samples of 12 patients in the MMRC dataset (5% of the total number of patients) were annotated incorrectly due to sample swaps and other unknown causes. Sample-labeling errors occur in clinics [87], clinical trials [88], and research databases [52]. Analyses based on error-containing datasets might decrease the power of the datasets, but may also lead to incorrect or contradictory scientific conclusions, or even harming patients [89,90].…”
Section: Discussionmentioning
confidence: 99%